Sintesis Bio-Pelumas Minyak Minyak Biji Jarak: Pengaruh Rasio Mol Dan Waktu Reaksi - Angelina Debbie; Irdoni Irdoni; Nirwana Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
A lubricant is an inseparable part of machine. Lubricants used to protect engine components from worn-out. Along with the increasing demands on materials that are environmentally friendly and renewable, vegetable oils or animal fats based Bio-lubricants can be claim as a solution. Castor oil is an oil that can not be consumed thus potentiallyy used as raw material for bio-lubricants. This research purposes to study the synthesis of bio-lubricants from castor oil to observe the effect of stirring speed and reaction temperature. The research was begun with the saponification of castor oil with 2 N KOH, the reaction temperature at 70 ° C. Solid formed was mixed with 10 N HCl and stirred for 20 minutes and then the formed fatty acid is separated from the rest of reactants. Furthermore, fatty acids will be esterified with etylen glycol on a stirring speed 180 rpm at 150C, with the variation of mole ratio: 1:3,1:4;1:5 and the reaction time: 2,4,6 hours . The highest yield is 91.15% at mole ratio 1:4 for 6 hours with a flash point 302°C, pour point 5°C, density 0.9005 g/ml and viscosity index amounted 145,596.Keywords: Bio-Lubricants, Castor Oil, Yield